Study of Lung Function of Sawmill Processed Wood Workers in Pasir Panjang Village - Andrew Stevant; Eti Kurniawati; Abul Ainin Hapis (Universitas Islam Negeri Alauddin Makassar, 2021)
Wood sawmill workers were at risk for impaired lung function, this is due to one of the work processes, namely sawing which produces wood dust. The previous survey showed about 60% of respondents had impaired lung function. The study aimed to determine associated factors of lung function of sawmill processed wood workers in the village of Pasir Panjang. This study was a quantitative with a cross sectional design. The research sample was 40 workers in the Processed Wood Sawmill, Pasir Panjang Village. The sample size was determined by the total population. Data analysis used chi square test. The results showed about 85.0% of respondents had abnormal lung function, 67.5% of respondents had a long working period, 55.0% of respondents smoked and 60% of respondents were at risk. Bivariate analysis showed there was a relationship between years of service (p-value=0.010) and age (p-value=0.029) with lung function in Processed Wood Sawmill workers in Pasir Panjang Village, Jambi City. There was no relationship between smoking habit and lung function in sawmill workers in Pasir Panjang, Jambi City (p-value=0.073). It was expected that the owner of the processed wood sawmill to measure the dust content at least once a year and install an exhaust fan with a large blower capacity in the production area